(untitled) (SCIENCE TIME JOURNAL, 2026)
In the context of digitalization and global information exchange, the translation of online texts has become one of the crucial components of cross-cultural communication. This article discusses the interconnected process of translation, editing, and post-editing in the production of online texts. Special attention is given to the strategies used by translators and the role of machine translation in the translation process.